Tribal "remnants" or state citizens: Mississippi Choctaws in the post-removal South*. Issue 2 (3rd May 2016) - Osburn, Katherine M. B.
ABSTRACT: This paper explores how the Mississippi Choctaws engaged state citizenship in the years immediately following removal. I challenge the standard narrative of Choctaws' relationships with the Mississippi legal system as one in which they were primarily victimized by unscrupulous lawyers and state officials. I argue instead that Choctaws used their new status as citizens to fight back against dispossession. I also examine how ideals of masculinity and class conflicts shaped interpretations of rights and obligations between Indians and whites.